2016
DOI: 10.1016/j.drugalcdep.2016.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Binge drinking and subsequent depressive symptoms in young women in Australia

Abstract: Extremely frequent binge drinking (more than weekly) in late adolescence appears to elevate the risk of subsequent depressive symptoms in young women in their early twenties and thirties, emphasising the need for preventive strategies to curb binge drinking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 63 publications
4
10
0
Order By: Relevance
“…In this study, data from a large national survey among adults were used to examine the association between MDE and AUD and the effects of socio-economic factors on this association. In agreement with several studies [7,[28][29][30][31][32][33] our study found a signi cant association between depressive disorder and AUD.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, data from a large national survey among adults were used to examine the association between MDE and AUD and the effects of socio-economic factors on this association. In agreement with several studies [7,[28][29][30][31][32][33] our study found a signi cant association between depressive disorder and AUD.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, data from a large national survey among adults were used to examine the association between MDE and AUD and the effects of socio-economic factors on this association. In agreement with several studies [5,19,20,4,[21][22][23] our study found a significant association between AUD and depressive disorder. Such significant and positive relationship could be explained in terms of shared common genetic and environmental factors in the comorbidity of alcohol-use disorder and depressive disorder, as investigated in other studies [24][25][26].…”
Section: Discussion Main Findings Interpretations and Comparisons Wisupporting
confidence: 93%
“…In this study, data from a large national survey among adults were used to examine the association between MDE and AUD and the effects of socio-economic factors on this association. In agreement with several studies [5,6,[25][26][27][28][29] our study found a signi cant association between depressive disorder and AUD. Such a signi cant and positive relationship could be explained in terms of shared common genetic and environmental factors in the comorbidity of depressive disorder and AUD, as investigated in other studies [30][31][32].…”
Section: Discussionsupporting
confidence: 93%